Korelasi Perilaku PSN dan Tempat Perindukan Nyamuk dengan Keberadaan Jentik Aedes Aegypti di Desa Jetak Kecamatan Wedarijaksa Kabupaten Pati - Priyantama, Elfrado Mosis; Yuliawati, Sri; Kusariana, Nissa; Martini, Martini (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
Dengue Hemorhagic Fever is cause by infections with the Dengue virus. DHF cases related to the presence of Aedes Aegypti larvae are influence by community behavior in preventing and eradicating dengue fever. Eradicating dengue mosquito larvae is known as eradicating mosquito nests (PSN) which is carried out using 3M, Biological and Chemical steps. The aim of this research is to determines the relationship between dengue PSN behavior and mosquito breeding sites and the presence of Aedes Aegypti larvae in Jetak Village, Wedarijaksa District, Pati Regency. This research is an analyctical observational study with a cross sectional approach with a sample of 102 respondent using the random sampling (SRS) method. Data analysis used univariate results and bivariate tests using Chi Square. These independent variables are PSN behavior, breeding places, and the presenced of Aedes Aegypti mosquito larvae. The research results show that based on the Chi Square test with= 5%, PSN behavior p < 0.001 (95% CI 0.098-0.137), and brooding place p < 0.001 (95% CI 0.098-0.140). The conclusiont of this research is that there is a relationship between PSN behavior and mosquito breeding places and the presence of Aedes Aegypti larvae in Jetak Village, Wedarijaksa District, Pati Tahum Regency in 2023.